2023
DOI: 10.1590/1678-4685-gmb-2022-0323
|View full text |Cite
|
Sign up to set email alerts
|

TMEM147 is a novel biomarker for diagnosis and prognosis of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common type of liver malignancy with high incidence and poor prognosis. Transmembrane protein 147 (TMEM147) has been implicated in the development of colon cancer. However, the role of TMEM147 in HCC remains unclear. In this study, data of 371 HCC tissues, 50 adjacent nontumor tissues, and 110 normal liver tissues were retrieved from the TCGA and GTEx databases. TMEM147 expression was found to be increased in HCC tissues. High expression of TMEM147 was related to poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Changes in gene expression play a significant role in the pathogenesis of cancer [ 7 12 , 14 , 19 21 ]. For instance, the overexpression of transmembrane protein 147 (TMEM147) was observed in patients with hepatocellular carcinoma, and elevated TMEM147 expression was linked to poor prognosis [ 14 ]. Similarly, alterations in gene expression were implicated in the development of glioma [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in gene expression play a significant role in the pathogenesis of cancer [ 7 12 , 14 , 19 21 ]. For instance, the overexpression of transmembrane protein 147 (TMEM147) was observed in patients with hepatocellular carcinoma, and elevated TMEM147 expression was linked to poor prognosis [ 14 ]. Similarly, alterations in gene expression were implicated in the development of glioma [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMEM115 is a membrane protein; notably, membrane proteins constitute 30% of human proteins and have been used as a physiological and pathological biomarker [10,11]. Fan et al found that increased TMEM147 expression was associated with poor prognosis [14]. Furthermore, LIHC has demonstrated the potential of transmembrane protein as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane proteins constitute 30% of the human proteins and are used as biomarkers in various physiological and pathological conditions [11]. In addition, Transmembrane proteins have been reported to novel biomarker for prognosis of LIHC [12][13][14]. However, the TMEM115, a transmembrane protein, has not been confirmed as a biomarker in LIHC; thus, its potential as a tumor biomarker must be confirmed.…”
Section: Introductionmentioning
confidence: 99%